Éducations à : penser l’articulation des savoirs et des valeurs au service de l’agir sociétal - Jean-Marc Lange (Éducation et Socialisation)
Education for sustainable development is indicative of the pedagogical and didactic questions about the "educations for". Knowledge and values are stressed in their relation to action and commitment advocated by international and national recommendations. The article aims to clarify these articulations and tensions in their reciprocal relations, and to make clear the doctrines. It thus contributes to the elaboration of curricular benchmarks for this educational field and lays down the principles of a didactic of societal action in relation to educational purposes, those of a participatory democracy.